[In search of the Asian loot ; Taxing tobacco ; Sailing in Boracay [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Charles McDougald of the Fort Santiago gold digging has come up with a book in gold wealth that lies burned under Philippine soil. Tackles issues on taxation for cigarettes. Sailing with or without wind in Boracay is exciting.